Archive Fever as Genealogical Fever: Coming Home to Scottish Archives - Little, Hannah (Archivaria, 2008)
This article explores the kind of “archivization” that is produced by family historians. Within this process, the function and meaning of archives in Scotland is changing and here is offered an examination of this transformation. Firstly, an overview of how family history has developed over time and its relation to the history of Scottish archives is provided. Secondly, the article investigates several themes within family history and tourism. These include an exploration of the Scottish diaspora and the idea of homecoming; a comparison of how the concept of authenticity is used within the tourist industry and archives; and finally a discussion on the role that archives play in the construction of identity. RÉSUMÉ Cet article examine le genre d’«archivation» qui est produite par les historiens de la famille. Dans ce processus, la fonction et le sens des archives en Écosse évoluent, et ce texte offre un examen de cette transformation. D’abord, il donne un aperçu de la façon dont l’histoire de la famille s’est developpée avec le temps, en traçant sa relation avec l’histoire des archives écossaises. Ensuite, l’article examine plusieurs thèmes reliés à l’histoire de la famille et au tourisme. Ceux-ci incluent un examen de la diaspora écossaise et de l’idée du retour chez-soi; une comparaison de la façon dont le concept de l’authenticité est appliqué dans l’industrie du tourisme et aux archives; et enfin, une discussion du rôle des archives dans la construction de l’identité.